2006
DOI: 10.1002/cncr.22330
|View full text |Cite
|
Sign up to set email alerts
|

Decline in serum carcinoembryonic antigen and cytokeratin 19 fragment during chemotherapy predicts objective response and survival in patients with advanced nonsmall cell lung cancer

Abstract: Objectives: The body adiposity index (BAI) is a proposed alternative to the body mass index (BMI) that has shown good cross‐sectional agreement with percent body fat (%BF) in validation studies. The objective of this study was to examine the ability of BAI to track adiposity change over time in a biracial sample of midlife women. Methods: African‐American (n = 159) and Caucasian (n = 206) women, aged 42–60 years, at the Chicago site of the Study of Women's Health Across the Nation were followed from 2002 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 51 publications
4
89
0
3
Order By: Relevance
“…The sensitivily of CYFRA21-1 was 55% -70% for lung cancer , and the specificity was 70% -80%. Therefore it is considered to be the best tumor marker in detection of lung squamous cell carcinoma (Ardizzoni et al, 2006). Our study demonstrated that the sensitivity of CYFRA21-1 in detecting lung cancer was 58.42%,the specificity was 91.52%.Level of CYFRA21-1 in serum of patients with lung cancer were significantly higher than those with lung benign disease and healthy controls suggesting the CYFRA21-1 is important in early diagnosis of lung cancer.…”
Section: Discussionmentioning
confidence: 61%
“…The sensitivily of CYFRA21-1 was 55% -70% for lung cancer , and the specificity was 70% -80%. Therefore it is considered to be the best tumor marker in detection of lung squamous cell carcinoma (Ardizzoni et al, 2006). Our study demonstrated that the sensitivity of CYFRA21-1 in detecting lung cancer was 58.42%,the specificity was 91.52%.Level of CYFRA21-1 in serum of patients with lung cancer were significantly higher than those with lung benign disease and healthy controls suggesting the CYFRA21-1 is important in early diagnosis of lung cancer.…”
Section: Discussionmentioning
confidence: 61%
“…Ardizzoni et al [41] outlined that a reduction in CEA and CYFRA 21-1 serum levels (≥ 20%) after 2 cycles of chemotherapy could be regarded as a possible surrogate marker of chemotherapy efficacy in patients with advanced NSCLC. Moreover, Nisman et al [42] reported that declination in CYFRA 21-1 levels (≥ 35%) after two cycles of chemotherapy could be a reliable marker for treatment efficacy and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Nisman et al (20) found that there was no correlation between radiologic OR and survival, while declines in serum CYFRA21-1 after 2 cycles of chemotherapy were closely related to survival. Ardizzoni et al (21) studied 107 patients with advanced NSCLC and also observed that declines in serum CYFRA21-1 and CEA were closely related to chemotherapy response and survival, whereas radiologic OR had no correlation with survival. Similar to previous studies, our study also demonstrated that the declines in serum CYFRA21-1 and CEA were closely related to chemotherapy response and survival, especially related to radiologic OR.…”
Section: Discussionmentioning
confidence: 99%